Feasibility and safety of transfemoral implantation of Edwards SAPIEN XT prosthesis without balloon valvuloplasty in severe stenosis of native aortic valve. Issue 5 (8th November 2013) - García, Eulogio; Martín, Patricia; Hernández, Rosana; Rodríguez, Victor; Fernández, Abelardo; Gama, Vasco; Almería, Carlos; Macaya, Carlos
<x xml:space="preserve">Abstract</x> Objectives Balloon valvuloplasty (BV) before transcatheter aortic implantation has been thought to be mandatory before the valve is implanted. We have explored the feasibility and safety of direct implantation of balloon expandable Edwards SAPIEN XT valve without prior balloon dilatation. Background Some complications after transcatheter aortic valve replacement (TAVR) have been associated with unwanted effects of BV, mainly the contribution to stroke and severe aortic regurgitation (AR) before the valve is implanted. Direct implantation with a self‐expanding aortic valve has been recently reported. Methods From November 2011 to April 2012, ten patients were selected that met the following criteria in the transesophageal echocardiography (TEE): moderate calcification, homogeneous distribution of calcium, symmetrical opening of the valve, and some degree of aortic insufficiency. Results All patients had symptomatic aortic stenosis of a native valve and high surgical risk; six patients had the valve mildly calcified, in four patients the degree of calcification was moderate. The native valve was crossed and the prosthetic aortic valve was properly positioned in all cases and implanted in the correct position. No patient underwent post‐dilatation and trivial AR was present in four patients. There were no adverse events (death, need for pacemaker, myocardial infarction, or stroke). At 30 days post‐procedure, all patients were alive and had significant clinical improvement. Conclusions Direct implantation of Edwards SAPIEN XT without prior BV in selected cases is feasible and safe. The number of patients in whom this technique would be applicable, and their impact on reducing complications has to be determined. © 2013 Wiley Periodicals, Inc.